Exploring school dropout among males in the greater Cape Town area, South Africa - Geldenhuys, Philip Rudolf (Department of Social Development, 2017)
The unofficial state of education in South Africa is announced annually by means of the Grade 12 results, also known as the National Senior Certificate. As a result, little attention is given to the more than half or at least 500 000 South African learners who drop out of the school system annually. Consequently, scholarly work dealing with topics relating to school dropout in South Africa is limited. This study moves the focus to a specific population group who are at risk of dropping out of school, namely male learners in poor communities. An exploratory qualitative study was undertaken to determine what the main factors are that are influencing school dropout among males in the greater Cape Town area of South Africa. The participants in this study included 49 key informants, including male school dropouts, teachers, school principals, representatives of the Western Cape Education Department, and parents of male school dropouts. Using in-depth individual interviews and focus group discussions, it was possible to establish that male school dropout is influenced by an array of factors of which some can immediately precede departure from high school while others could have happened years earlier in primary school or even before. The thesis established in this dissertation is that most of the influences on male school dropout are primarily institutional. In other words, the underlying narrative emphasising male school dropouts as the main contributors to this outcome is misleading. Indeed, most of these influences are amplified by practices within the institutional context, especially the school. A localised theoretical framework for male school dropout in South Africa is constructed with the support of Rumberger and Lim' s (2008) conceptual framework and can be understood within the school dropout models of both Finn (1989) and Tinto (1975). Furthermore, the total absence of school dropout records and statistics on a school and local district level keeps role players unaccountable for this action. As a result, teachers, school principals and Western Cape Education Department representatives are either ignorant of or paralysed by the complexities and extent of school dropout among males. Therefore, this study aims to lay the foundation for further research to inform and empower the aforementioned role players to address this problem.